A review on nanomaterials as additive in asphalt binder - K. A., Masri; Nur Syafiqah, S. M. Z.; M. A., Seman; P. J., Ramadhansyah; H., Yaacob; N., Mashros (IOP Publishing, 2021)
Nowadays pavement tends to experience extra loadings and deteriorates faster than expected. There are various ways that has been done in order to withstand permanent deterioration such as adding fibers, polymers and waste materials. Some shows a good enhancement in the terms of fatigue life and dynamic creep. Nanotechnology is being expanded in the highway area thus, nanomaterials such as nano silica, nano clay, iron oxide nanoparticles and others are being incorporated in asphalt as modifier or additives. Some of the nanomaterials improves the mechanical performance of asphalt mixture and increase fatigue life. This review paper discusses the advantages of using nanomaterials in asphalt as an additive